Case Report: Tocilizumab Treatment for VEXAS Syndrome With Relapsing Polychondritis: A Single-Center, 1-Year Longitudinal Observational Study In Japan - Kunishita, Yosuke; Kirino, Yohei; Tsuchida, Naomi; Maeda, Ayaka; Sato, Yuichiro; Takase-Minegishi, Kaoru; Yoshimi, Ryusuke; Nakajima, Hideaki (Frontiers in Immunology, 2022)
Abstract VEXAS syndrome is an autoinflammatory disease caused by somatic variants in the UBA1 gene that lead to severe systemic inflammation and myelodysplastic syndrome. Although no standard therapy has been established yet, azacitidine and bone marrow transplantation have been reported to be promising possibilities; however, the indications for these treatments are problematic and not necessarily applicable to all patients. We previously reported the results of short-term treatment with tocilizumab (TCZ) and glucocorticoids in three patients with VEXAS syndrome. In this letter, we report that the combination of TCZ and glucocorticoids allowed the patients to continue treatment for at least one year without significant disease progression. Glucocorticoids were able to be reduced from the start of TCZ. Adverse events were herpes zoster, skin ulceration after cellulitis, and decreased blood counts. The results suggest the significance of this treatment as a bridge therapy for the development of future therapies.